Peran Zakat dan Pembiayaan Syariah bagi UMKM dalam Mewujudkan Sustainable Development Goals (SDGs) - Faurani Santi Singagerda; Asmaria Asmaria (ITB AAS INDONESIA Surakarta, 2023)
This research is motivated by the importance of realizing the Sustainable Development Goals (SDGs). This study aims to find out and analyze the Role of Zakat and Sharia Financing for MSMEs in Realizing Sustainable Development Goals (SDGs). This research is a descriptive research with a qualitative approach. This research uses field research and library research.. Sources of data in this study are primary data and secondary data. The population of this study were ZIS fund managers (Zakat, Infaq, and Sadaqah within the National Zakat Amil Agency (BAZNAS) of Bandar Lampung City and BSI employees of Bandar Lampung City. The sample in this study were 5 BAZNAS staff of Bandar Lampung City and 5 employees BSI City of Bandar Lampung Data collection techniques in this study used observation, interviews and documentation The data collected was then processed and analyzed qualitatively The results of this study explain that 1) the role of zakat is to distribute and utilize zakat funds to increase people's income so that they can used as capital to establish MSMEs, and 2) the role of sharia financing, which is to assist MSME players in meeting their capital needs so that the business they run can develop and have an impact on their welfare.